New concept for the value function of prospect theory - Kazuo Sano (Quantitative Finance and Economics)
In prospect theory, the value function is typically concave for gains and convex for losses, with losses usually having a steeper slope than gains. The neural system responds differently to losses and gains. Five new studies on neurons related to this issue have examined neuronal responses to losses, gains, and reference points. This study investigated a new concept of the value function. A value function with a neuronal cusp may exhibit variations and behavioral cusps associated with catastrophic events, potentially influencing a trader's decision to close a position. Additionally, we have conducted empirical studies on algorithmic trading strategies that employ different value function specifications.